Estimativas de autovalores via módulo de continuidade para a equação do calor - Silva, Robson dos Santos (2015)
We bound the modulus of continuity of solutions to quasilinear parabolic equations in terms of the initial modulus of continuity and elapsed time. In particular, applying this to the heat equation with Neumann boundary conditions, we get a positive lower bound for the first positive eigenvalue of the Laplacian on bounded convex domains in Euclidean space.